How normalised is HIV care in the UK? A survey of current practice and opinion. (17th January 2007) - Rutland, E; Foley, E; O'Mahony, C; Miller, R F; Maw, R; Kell, P; Rowen, D
Abstract : Objectives: The prognosis for individuals infected with HIV has changed dramatically over the past 10 years, with patients living longer and requiring other specialist services. It is apparent that access of other healthcare professionals to clinical information about a patient's HIV care differs between centres in the UK. Lack of awareness of an individual's HIV status may compromise their clinical care. Aim: To establish current practice and identify the views of clinicians caring for patients infected with HIV. Methods: Lead consultants in all genitourinary medicine departments in the UK were invited to complete a questionnaire regarding use of combined HIV and hospital notes and ability of general practitioners and other hospital specialists to access information about individual patient's HIV care. Clinician's opinions on the "normalisation" of HIV management were also sought. Results: Combined notes (outpatient and inpatient) were used by 12% (16/130) of respondents. The patient's identifying number was used to request blood tests in 86%. Of the respondents, 42% had encountered difficulties in communication that affected delivery of care for an HIV-positive patient. Conclusions: Centres using combined notes identified a higher frequency of communication with other doctors and specialties, suggesting a higher standard of care. Physicians involved in HIV care should consider combining patients' HIV and hospital notes for improved clinical care.